(3GdSjQI GdTQjaI GdefUhQjIs - (3CHh aQGS Hf OZfe,J (B615 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi JWGgQ BdGFg hMSf HdGFg deG GfJgi GdLRA GdChd ef bUI ESeGYjd Hf WZfcjf ZHJOC gPG GdLRA HPcQ GdbUU hGdMhGOK hLYdJ Pdc eJUdkG HJGQjN GdLRA GdChd GdPi gh fUa TYHGf s
(3BNQgG (B:s
(3bGd JYGdi (B( (3hLYdfGge CFeI jgOhf HCeQfG deG UHQhG (B) (3aEPG UHQ GdEfSGf hfUM ESJMb ef GdNGdb GdKhGH hef GdeNdhb GdKfGA bO WGd GdTQM hGdMeO ddg Ydi cd MGd Je GdLRA GdKGfi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs